Plasmodium falciparum msp1 and msp2 genetic diversity in parasites isolated from symptomatic and asymptomatic malaria subjects in the South of Benin - Lagnika, H.O.; Moussiliou, A.; Agonhossou, R.; Sovegnon, P.; Djihinto, O.Y.; Medjigbodo, A.A.; Djossou, L.; Amoah, L.E.; Ogouyemi‑Hounto, A.; Djogbenou, L.S. (Springer, 2022)
Symptomatic and asymptomatic malaria patients are considered as the reservoirs of human Plasmodium. In the present study, we have evaluated the Plasmodium falciparum merozoite surface protein-1 (Pfmsp1) and protein-2 (Pfmsp2) genetic diversity among the symptomatic and asymptomatic malaria infection from health facilities in Cotonou, Benin Republic. A cross-sectional study recruited 158 individuals, including 77 from the asymptomatic and 81 from the symptomatic groups. The parasites were genotyped using Nested Polymerase Chain Reaction. Samples identified as Plasmodium falciparum were genotyped for their genetic diversity. No significant difference was observed in the overall multiplicity of infection (MOI) between the asymptomatic and symptomatic groups. In the symptomatic group, the overall frequency of K1, MAD20, and RO33 allelic family was more predominant (98.5%) followed by 3D7 (87.3%) and FC27 (83.1%). However, in asymptomatic group, the K1 alleles were the most prevalent (100%) followed by FC27 (89.9%), 3D7 (76.8%), MAD20 (60.5%), and RO33 (35.5%). The frequency of multiple allelic types (K1+MAD20+RO33) at the Pfmsp1 loci in the symptomatic infections was significantly higher when compared to that of the asymptomatic ones (97% vs. 34%, p<0.05), whereas no difference was observed in the frequency of multiple allelic types (3D7 and FC27) at the Pfmsp2 loci between the two groups. The high presence of msp1 multiple infections in the symptomatic group compared to asymptomatic ones suggests an association between the genetic diversity and the onset of malaria symptoms. These data can provide valuable information in the development of a vaccine that could reduce the symptomatic disease.
Research Article
Keywords: Malaria; Asymptomatic; Symptomatic; Genetic diversity; South of Benin